Using Domain Decomposition Method and Non-Matching Grids for Solving Some Variational Inequalities - M.A. Ignatieva; A.V. Lapin (Учёные записки Казанского университета: Серия Физико-математические науки, 2015)
Finite difference approximations and iterative solution methods are constructed for a class of variational inequalities with constraints imposed on the solution and a priori known subdomain containing a free boundary. Domain decomposition method and non-matching grids are used for the approximation. Splitting and Uzawa-type iterative methods are investigated for solving the approximated problems. Numerical comparison of their efficiency is carried out.